Constrained purchase decision-making process at the base of the pyramid. Issue 1 (31st January 2019) - Choudhury, Nanda; Mukherjee, Srabanti; Datta, Biplab
Abstract : Purpose: The purpose of this paper is to examine the factors affecting decision-making at the BoP and propose a framework of the consumer decision-making process at the base of the pyramid (BoP). Design/methodology/approach: The qualitative research design was adopted to collect primary data. Data collected through the in-depth semi-structured interviews of the 48 BoP consumers in Kolkata and Kharagpur (India) were subjected to grounded theory analysis for theory development. Findings: This study reveals that consumer vulnerability affects the decision-making process and the transaction cost at BoP level. It was observed that the consumers at the BoP make constrained choices due to their vulnerability and try to minimise transaction cost while selecting the retails. The constrained retail choice leads to a limited selection of products and brands. Originality/value: This study, for the first time, has investigated the decision-making process for BoP consumers in detail. As a pioneering attempt, it sheds light on some new factors including consumer vulnerability and transaction cost that have an impact on the consumer decision-making process.